(Nekateri) izzivi prava in pravne fakultete v sodobnem svetu - Zagorc, Saša (Javna uprava, 2022)
The contribution is a slightly modified address of the Dean of the Faculty of Law of the University of Ljubljana Professor Saša Zagorc at the traditional New Year’s reception of the Faculty of Law in Ljubljana on 16 December 2022. The author briefly tackles three challenges that, in his opinion, we will face in the future: the role of law in the time of expansion of artificial intelligence, weaker perception of law in society, adapting legal studies to the new reality. Among other things, the author advocates for the humanisation of artificial intelligence. In his view, the joint efforts of lawyers must lead to a constant delicate search for a balance between procedural justice and administrative efficiency. At the same time, he calls for the study of law to be made even more perspective, and he sees the role of the Faculty of Law of the University of Ljubljana as crucial in this regard in Slovenia.
Keywords: artificial intelligence; dean; law; law faculty; law studies; Pravna fakulteta; pravo; speech; študij prava; umetna inteligenca; University of Ljubljana; Univerza v Ljubljani